2016
DOI: 10.2147/ott.s108599
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of the prognostic value of abnormally expressed lncRNAs in hepatocellular carcinoma

Abstract: Many long noncoding RNAs (lncRNAs) have been reported to be abnormally expressed in hepatocellular carcinoma (HCC), and may have the potential to serve as prognostic markers. In this study, a meta-analysis was conducted to systematically evaluate the prognostic value of various lncRNAs in HCC. Eligible literatures were systematically collected from PubMed, Embase, Web of Science, and Cochrane Library (up to December 30, 2015). The main outcomes including overall survival, relapse-free survival, and disease-fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 48 publications
(74 reference statements)
0
13
0
Order By: Relevance
“…An increasing amount of evidence has revealed that different LncRNAs might be associated with HCC [11]. With regard to these latter effects, previous molecular-based studies found that certain LncRNAs promote tumor initiation, cancer cell growth, and metastasis during the development of HCC [12][13][14]. Human ovarian cancer-specific transcript 2 (HOST2) was once reported to be specifically expressed at a high level in human ovarian cancer [15].…”
Section: Introductionmentioning
confidence: 99%
“…An increasing amount of evidence has revealed that different LncRNAs might be associated with HCC [11]. With regard to these latter effects, previous molecular-based studies found that certain LncRNAs promote tumor initiation, cancer cell growth, and metastasis during the development of HCC [12][13][14]. Human ovarian cancer-specific transcript 2 (HOST2) was once reported to be specifically expressed at a high level in human ovarian cancer [15].…”
Section: Introductionmentioning
confidence: 99%
“…The patients with a higher level of lncRNA Sox2ot expression had a reduced DFS and OS time. A previous meta-analysis of the prognostic value of various abnormally expressed lncRNAs in HCC demonstrated that the transcription level of various lncRNAs was significantly associated with the tumor size, microvascular invasion and portal vein tumor thrombus, and may serve in the prognostic evaluation of patients with HCC (6). In another previous study, lncRNA Sox2ot expression was associated with T stage, distant metastasis, differentiation and a poorer OS and DFS time in breast cancer (17).…”
Section: Discussionmentioning
confidence: 95%
“…Long non-coding RNAs (lncRNAs) are ~200 nt to 100 kb long and have emerged as key regulators in the majority of biological processes (4,5). Previous studies have demonstrated that lncRNAs participate in a number of tumor processes and may be suitable as therapeutic targets and biomarkers for predicting the prognosis of patients (6,7). For example, the expression of PCAT-1 was observed to be significantly increased in HCC tissues, and was significantly associated with the OS time of patients with HCC (8).…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, they found that altered lncRNAs were associated with poor survival outcomes in renal cell carcinoma, osteosarcoma, and hepatocellular carcinoma. [ 48 50 ] Luo et al [ 51 ] also performed a meta-analysis to investigate the prognostic value of abnormally expressed lncRNAs in ovarian cancer. In their study, 2 studies using microarray data were included [ 29 , 31 ] ; however, we did not include any studies using microarray data.…”
Section: Discussionmentioning
confidence: 99%